Caracterização e conservação da população de Folículos Ovarianos pré antrais de catetos (Tayassu tajacu, Linnaeus, 1758) - Lima, Gabriela Liberalino (Universidade Federal Rural do Semi-Árido, 2011)
It were done the estimative of the follicular population of the collared peccaries ovaries and the short term preservation of it using PBS or ACP. Pair of ovaries from 6 females were collected. A half of one ovary was designated to the estimative and characterization of the follicle population, and it was immediately submitted to histology and transmission electron microscopy (TEM). The other ovary was divided into 9 fragments and one of it was immediately submitted to histology procedures, the other fragments were stored either in phosphate-buffered saline (PBS; control group) or ACP medium in isothermal Styrofoam boxes containing biological ice packs. The boxes were sealed and opened only after 12, 24, or 36 h. After opening each box, the ovarian fragments were submitted to histological analysis and TEM. The temperature into the boxes and pH of the medium were checked. A total of 33273.45 ± 3019.30 preantral follicles (PF) were estimated for each ovary. Most of them was morphologically normal (94.4%) and just a few was atretic (5.6%). At histological analysis, a lot of lipids droplets was observed at oocyte cytoplasm, which was confirmed by TEM. About short term storage, it was observed that the follicular integrity was kept until 4 h, using ACP medium. The medium pH was kept constant. This work shows, for the first time, the estimative of the PF population of the ovary, totally and in each follicle category, and it´s characterization in collared peccaries (Tayassu tajacu). It could be concluded that the ACP medium may be used as an alternative medium for the short term preservation of PF in that specie.
CHARACTERIZATION AND CONSERVATION OF THE OVARIAN PREANTRAL FOLLICLES POPULATION OF COLLARED PECCARIES (Tayassu tajacu, Linnaeus, 1758)
Keywords: Tayassu tajacu; Preantral follicles; follicular population; short term preservation; ACP medium; Tayassu tajacu; folículos Pré Antrais; população folicular; refrigeração; ACP; CIENCIAS AGRARIAS::MEDICINA VETERINARIA